Epidemiology of drug hypersensitivity reactions using 6-year national health insurance claim data from Korea - Han, Jae Eun; Ye, Young Min; Lee, Sukhyang (International Journal of Clinical Pharmacy, 2018)
Background Drug hypersensitivity reactions (DHRs) constitute a large portion of adverse drug reactions (ADRs), but studies for DHR incidence based on national data are scarce. Objective This study aimed to estimate the incidence and patterns of DHRs in a Korean population and the associated utilization of medical resources using the national claims data. Setting The retrospective cohort study performed using the national insurance claim database of the Health Insurance Review and Assessment (HIRA) in Korea. Methods The International Classification of Disease 10th revision code was used to identify DHRs with 20 drug induced DHR codes. The claim data with a diagnosis of DHR in the 2009-2014 periods were analyzed. Main outcome and measure The annual incidence and the 6-year incidence rates were calculated. Incidence rate coefficients were analyzed by sex, age, and year. DHRs following with visits of emergency department (ED) or intensive care unit (ICU) were assessed for utilization of medical resources and risk of ER or ICU visits by sex and age Results A total of 535,049 patients with 1,083,507 claims were assessed in the HIRA database for 6 years. DHR incidence was high in the elderly. The risk of ED and ICU visit with DHR was also higher in the elderly than in the young [highest relative risk, RR of ED 2.59 (1.65–4.07), ICU 5.04 (2.50–10.18)]. DHRs related to blood were high in the young age. Conclusion Incidence of DHRs in the real-world clinical practice was higher in the elderly and female. Clinical consequence was more severe in the elderly.
Keywords: Adolescent; Adult; Age Factors; Aged; Cohort Studies; Databases, Factual; Drug Hypersensitivity; Drug-Related Side Effects and Adverse Reactions; Emergency Service, Hospital; Female; Humans; Incidence; Intensive Care Units; Male; Middle Aged; National Health Programs; Republic of Korea; Retrospective Studies; Risk; Sex Factors; Young Adult; Adverse drug reactions (ADRs); Drug hypersensitivity; Health insurance database; Incidence; Korea